Actual and future digital threats and their impact on civil and military cybersecurity management - Negulescu Oriana Helena; Doval Elena; Stefanescu Ana Roxana (2022)
(1) What is the hacker community made up of and what are the main vulnerable industries? (2) What are the main types of digital threats and how are they characterized? (3) What are the vulnerabilities and damage caused by cyber-attacks? (4) What are the ways to detect digital threats? (5) What measures can be taken to prevent and avoid these attacks? (6) What does the cyber security management process consist of? (7) What cybersecurity evidence and trends can be selected?